The Effect Of Village Government Accountability And Transparency On Community Participation In Village Infrastructure Development - Nupsi, Nupsi; Kresnawati, Kresnawati; Nasution, Suswati (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi, 2025)
This study aims to determine the effect of village government accountability and transparency on community participation in village infrastructure development. The background of this research lies in the importance of implementing good governance principles at the village level, particularly in ensuring transparent and accountable management of village funds to encourage active community involvement. This research employs a quantitative approach using a survey method, distributing questionnaires to 90 respondents in Pulau Kemuning Village, Sungai Are District, in 2025. The independent variables are accountability (X₁) and transparency (X₂), while the dependent variable is community participation (Y). The results of multiple linear regression analysis show that, partially, accountability has a positive and significant effect on community participation, with a t-value of 8.400 > 1.997 and a significance level of 0.000 < 0.05. Similarly, transparency also has a positive and significant effect, with a t-value of 3.732 > 2.447 and a significance level of 0.000 < 0.05. Simultaneously, both variables have a positive and significant effect on community participation, as indicated by an F-value of 145.896 > 3.10 and a coefficient of determination (R²) of 0.770, meaning that 77% of the variation in community participation is explained by accountability and transparency. These findings indicate that enhancing accountability and transparency in managing village finances and development activities strengthens public trust and encourages more active community participation in village infrastructure development.